New GOLD COPD Guideline 2019: How We Deal with It? (Inhaled Corticosteroid Use and Blood Eosinophil Count) - Ari Julian Saputra; Kiki Widyastuti; Yusup Subagio Sutanto (Respiratory Science, 2021)
Background: Blood eosinophils may predict response to inhaled corticosteroids (ICS) in chronic obstructive pulmonary disease (COPD), where ICS is recommended in patients at high risk of exacerbations by the Global Initiative for COPD (GOLD) strategy. It can help clinicians to estimate the likelihood of beneficial preventive responses to the addition ICS to regular bronchodilator treatment, and thus can be used as a biomarker in conjunction with clinical assessment when making decisions regarding ICS use. This study aims to compare therapeutic data with blood eosinophil count in COPD patients. Methods: Data were collected from consecutive COPD outpatients in Bukit Asam Medika Hospital starting from March 1st, 2019 until June 30th, 2019 and dr. H. Mohamad Rabain Hospital starting from Oct 1st, 2019 until Dec 27th, 2019. We collected demographics, anthropometrics, smoking history, therapy, dynamic lung volumes, the Medical Research Council scale (MRC), CAT score, and blood eosinophil count. Results: From 57 data collected, 24 (42,1%) patients were having blood eosinophil count ≥300. Patients who have more exacerbation in COPD Group C were 33,3% and 63,2% in COPD Group D. The proportions of ICS-treated COPD Group D patients and blood eosinophil count of <300 and ≥300 was 63,9% and 36,1%, respectively. Conclusion: This study may provide information and characteristic of COPD patient in Indonesia rural area and showed who may have benefit to ICS therapy based on recommendation GOLD COPD 2019. Blood eosinophils counts is a low-cost biomarker and may help clinicians to made decision therapy.